DUTIES OF A UNIT BELONGING TO THE PUBLIC FINANCE SECTOR WITH RESPECT TO DOCUMENTATION OF MANAGEMENT AUDIT - Anna Mucha (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The paper discusses the issue of control in the public finance sector. The issue in question is particularly important in the context of transition from heavily bureaucratic financial control of the public finance sector entities used so far to the management control based on regulations observed in the commercial sector. The paper underlines the essence and the concept of the analyzed phenomenon s as well as legal regulations and standards constituting the management control. The management control solutions applicable in the public finance sector are presented. The applicable regulations and standards form an ordered set of guidelines which persons responsible for functioning of the management control should use to create, evaluate and improve management control systems. The purpose is to promote the implementation of coherent and standard management control model based on international standards in this field with taking into consideration specific unit tasks and conditions. The implemented regulations should be valid and adequate to a situation present in the entity. The obligations of the entities in the scope of management control documentation, which arise from standards in force, are underlined.